CVD on Optical Fibers: Tilted Fiber Bragg Gratings as Real‐time Sensing Platforms. Issue 1 (8th October 2014) - Mandia, David J.; Zhou, Wenjun; Albert, Jacques; Barry, Seán T.
Abstract: The tilted fiber Bragg grating (TFBG), as a versatile and robust tool for many sensing applications with a particular focus on vapor deposition processes, is reviewed. Recent work employing the TFBG as an optical probe for monitoring the metal‐organic (MO)CVD of noble‐metal, single‐source precursors is discussed extensively. This work also establishes the broad scope that utilizes TFBGs and other optical fiber configurations to interrogate thin film growth and the associated optical properties. While it cannot possibly cover the full scope of applications with respect to the TFBG device, this review highlights the recent advances of TFBG‐based sensing for CVD, and progress towards the applicability of TFBGs as evanescent field‐based sensors. Abstract : This review highlights optical fiber‐based, tilted fiber Bragg grating (TFBG) devices as sensors in the real‐time monitoring of group 11 (Cu, Ag, Au) metal‐organic (MO) and pulsed ( p ) ‐ CVD). This new in‐situ optical probe, while both a substrate and sensor, detects the nucleation and growth of metal and metal oxide thin films based on local refractive index changes of the TFBG under S‐ and P‐polarized core‐guided light. The coated TFBGs have many promising applications in plasmonic sensing and optoelectronics.